2015
DOI: 10.1002/ijc.29875
|View full text |Cite|
|
Sign up to set email alerts
|

Lung cancer treatment is influenced by income, education, age and place of residence in a country with universal health coverage

Abstract: Selection of lung cancer treatment should be based on tumour characteristics, physiological reserves and preferences of the patient. Our aims were to identify and quantify other factors associated with treatment received. Lung cancer patient data from 2002 to 2011 were obtained from the national population-based Cancer Registry of Norway, Statistics Norway and the Norwegian Patient Register. Multivariable logistic regression examined whether year of diagnosis, age, sex, education, income, health trust, smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
2
33
0
4
Order By: Relevance
“…This difference was no longer evident after adjustment for clinical features at the time of diagnosis. Other studies have shown that lower educational attainment predicts poorer outcomes in patients with NSCLC . Our study extends such work by assessing patient‐reported educational attainment rather than imputing educational attainment by geocoded address data at an area‐ or census‐tract level.…”
Section: Discussionmentioning
confidence: 82%
“…This difference was no longer evident after adjustment for clinical features at the time of diagnosis. Other studies have shown that lower educational attainment predicts poorer outcomes in patients with NSCLC . Our study extends such work by assessing patient‐reported educational attainment rather than imputing educational attainment by geocoded address data at an area‐ or census‐tract level.…”
Section: Discussionmentioning
confidence: 82%
“…A relationship has been indicated between ethnicity, socioeconomic status and the incidence and mortality from lung cancer. This was confirmed in a Norwegian study, investigating how type of lung cancer treatment was influenced by income, education and place of residence [16]. In a country with public health service providing universal tax-supported health care, guaranteeing unconstrained access to general practitioners and hospitals, the survival differences may be regarded as unexpected [17].…”
Section: Etiology Of Lung Cancermentioning
confidence: 87%
“…We applied the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) statement guidelines when reporting the three observational studies (16). All p values were two-sided, and a p value of less than 0.05 was considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…We consider this to be one possible explanation, as received treatment has been found to be associated with higher socio-economic status, despite Norway being a highly egalitarian country, with a free, universal health-care system [61]. …”
Section: Discussionmentioning
confidence: 99%